2019 International Joint Conference on Neural Networks (IJCNN) 2019
DOI: 10.1109/ijcnn.2019.8851859
|View full text |Cite
|
Sign up to set email alerts
|

Distant Pedestrian Detection in the Wild using Single Shot Detector with Deep Convolutional Generative Adversarial Networks

Abstract: In this work, we examine the feasibility of applying Deep Convolutional Generative Adversarial Networks (DCGANs) with Single Shot Detector (SSD) as data-processing technique to handle with the challenge of pedestrian detection in the wild. Specifically, we attempted to use in-fill completion (where a portion of the image is masked) to generate random transformations of images with portions missing to expand existing labelled datasets. In our work, GAN's been trained intensively on low resolution images, in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It produces images of pedestrians in unusual scenarios and positions, helping traditional object detection models to improve their ability to detect pedestrians. Dinakaram and colleagues [17][18][19] used another known and proven ability of Deep Convolutional GAN: an image resolution improvement. All three works combine the GAN's image resolution improvement with SSD to increase its pedestrian detection capabilities in different sizes and distances.…”
Section: Resultsmentioning
confidence: 99%
“…It produces images of pedestrians in unusual scenarios and positions, helping traditional object detection models to improve their ability to detect pedestrians. Dinakaram and colleagues [17][18][19] used another known and proven ability of Deep Convolutional GAN: an image resolution improvement. All three works combine the GAN's image resolution improvement with SSD to increase its pedestrian detection capabilities in different sizes and distances.…”
Section: Resultsmentioning
confidence: 99%
“…Pedestrian Detection [16] GAN for synthetic data creation [17] DCGAN + SSD [18] DCGAN + SSD [19] DCGAN + SSD Small Object Detection [20] Faster R-CNN + GAN [21] GAN + CNN + SSD/Faster R-CNN [22] CNN + ResNet + GAN Unsupervised Bounding Box Detection [23] CNN + GAN + Reinforcement Learning [24] Dilated CNN + GAN with Mask Mean Loss [25] Encoder + Conditional GAN 2.56 SSD300 Pascal VOC 2007 [16] Not Applicable Not Applicable Not Applicable [17] 45.2 SSD CIFAR-10/100 [18] 39.4 SSD VOC [19] Not Applicable Not Applicable Not Applicable [20] 19.47 Faster R-CNN Tsinghua-Tencent 100K [21] 25.1 FRCNN COWC Dataset [22] 60 Faster R-CNN (Small Objects) Tsinghua-Tencent 100K [23] Not Applicable Not Applicable Not Applicable [24] 5.37 [23] Car (Stanford) [25] 2.6 WCCN VGG16 VOC2007…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
“…[17], [18] and [19] use another very known and proven ability of Deep Convolutional GAN's which is images resolution improvement. All the three works combine the GAN's image resolution improvement with SSD to increase its pedestrian detection capabilities in different sizes and distances.…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
“…In our recent work [11], it was evidenced that image quality can critically impact on object detection. In [12], we exploited a DCGAN (deep convolutional generative adversarial network) [13] for image enhancement, as shown in Figure 2, and we found that such an enhancement scheme could help alleviate the serious degradation of object detection caused by low-quality images. In this paper, we aimed to leverage our initial discovery and apply such a DCGAN-based framework [12] for undersea/subsea object detection using a single-shot detector (SSD) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In [12], we exploited a DCGAN (deep convolutional generative adversarial network) [13] for image enhancement, as shown in Figure 2, and we found that such an enhancement scheme could help alleviate the serious degradation of object detection caused by low-quality images. In this paper, we aimed to leverage our initial discovery and apply such a DCGAN-based framework [12] for undersea/subsea object detection using a single-shot detector (SSD) [14]. This combinational framework DCGAN+SSD can help object detection in underwater environments by engaging DCGAN for image conversion, after which the object detector is applied to the converted images.…”
Section: Introductionmentioning
confidence: 99%